Enhancing Business Communication Skills in Vocational Education: A Generative Ai Approach for Personalized Learning - Wijayati, Titik; Safitri, Yulita Dwi; Hayatie, Marliza Noor (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
In the realm of higher education, there is an increasing emphasis on holistic education approaches that extend beyond academic achievements to encompass various dimensions of student well-being, including social, ethical, spiritual, civic, intellectual, and physical health. This paper explores the growing intersection between student mental health and generative artificial intelligence (AI), examining the potential of AI to enhance holistic education by providing personalized mental health support. The study highlights the eco-holistic model's advocacy for a